2022
DOI: 10.47176/mjiri.36.85
|View full text |Cite
|
Sign up to set email alerts
|

Bell's Palsy and COVID-19 Vaccination: A Systematic Review

Abstract: Bell's palsy is a rare complication reported after COVID-19 vaccination. Given the importance of neurological manifestations, the necessity to highlight and scrutinize the incidence of them following vaccination is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 40 publications
3
7
0
Order By: Relevance
“…The average time from vaccination to onset of symptoms amongst the cases in our review was 11.49 (11.064) days. This is consistent with previous studies by Shahsavarinia et al [ 10 ] that mentioned the onset of symptoms of bell’s palsy at around 10 days post-vaccination. On the other hand, our study represented that (62.8%) of the patients had unilateral-side complaints.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The average time from vaccination to onset of symptoms amongst the cases in our review was 11.49 (11.064) days. This is consistent with previous studies by Shahsavarinia et al [ 10 ] that mentioned the onset of symptoms of bell’s palsy at around 10 days post-vaccination. On the other hand, our study represented that (62.8%) of the patients had unilateral-side complaints.…”
Section: Discussionsupporting
confidence: 94%
“…Although there was no statistically significant difference concerning the prognosis and most of the comorbidities, patients without hyperuricemia or hypertension had a high rate of full recuperation in comparison with patients with these diseases. Our findings are in the same direction as the former reviews performed by Sriwastava et al [ 50 ] and Shahsavarinia et al [ 10 ] in terms of the association between the type of vaccines and the incidence of facial palsy. Unlikely, Khurshid et al [ 49 ] reported that most of the cases had bell’s palsy after taking the AstraZeneca vaccine.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…PTS is typically characterized by sudden, severe unilateral shoulder pain often with associated weakness and paresthesias. The pain has been described as constant and not positional in nature, and is generally self-limiting, lasting 1 to 2 weeks on average, although weakness may last for several months 1,2 . The patient ref-erenced above presented with a more chronic case of PTS and was symptomatic for roughly 3 months.…”
Section: Discussionmentioning
confidence: 99%